PLATONAS: FILOSOFAVIMO SUBJEKTO STRUKTŪRA IR DINAMIKA. - JANKAUSKAS, SKIRMANTAS (Logos: A Journal, of Religion, Philosophy Comparative Cultural Studies & Art (08687692), 2026)
The article discusses the development of the structure and functions of the subject of philosophizing - the soul - from the Sophists to Plato. It is stated that the Sophists initiated the differentiation of the subject of holistic thinking and defined the subject of everyday thinking, thereby complicating not only access to being, but also the possibility of written philosophizing. Socrates, relying on introspection, became aware of the imperative calling for caring for the goodness of the soul and opened up the possibility of defining an alternative dimension of the soul. In order to restore access to being, Plato in the Phaedo substantiated the epistemological and ontological kinship of the soul, supplemented by the aspect of ethics, with unchanging entities, and thus potentially with being. In the Banquet, by situating philosophizing within the loving relationship founded upon the value of beauty, Plato universalized and legitimized the Socratic practice of philosophy as a novel mode of philosophizing. Finally, in Phaedrus, Plato reconstructed the soul as a multi-layered structure and predicted that it, guided by the values of beauty and goodness, could thematize being. The article concludes by stating that Plato's reasoning potentially provides an alternative definition of being to the Parmenidean one.